2004
DOI: 10.1051/0004-6361:20035752
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of CO abundance to extinction andN(H$\mathsf{_{2}}$):

Abstract: Abstract.We have studied the ratio of 13 are given. These ratios were found to vary from cloud to cloud so that they are larger in B 335 than in B 133 and L 466. These variations are thought to primarily arise from variations of the column density ratio of CO and its isotopes to H 2 . The alternative explanation in terms of the N(H 2 )/A J ratio being larger in starforming regions (B 335) than in more quiescent regions lacking star formation (B 133 and L 466) appears less likely. We also discuss the evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
4
24
0
Order By: Relevance
“…N H 2 is the molecular hydrogen column density obtained using the relation N H 2 ¼ 1:1 ; 10 4 N 12 by Frerking et al (1982) for the Taurus cloud; this result is consistent with more recent determinations, summarized by Harjunpää et al (2004), for other nearby dark clouds. Table 1 summarizes our results for the mass of the outflowing gas in the various regions previously defined, tabulated .…”
Section: Outflow Mass and Energysupporting
confidence: 90%
“…N H 2 is the molecular hydrogen column density obtained using the relation N H 2 ¼ 1:1 ; 10 4 N 12 by Frerking et al (1982) for the Taurus cloud; this result is consistent with more recent determinations, summarized by Harjunpää et al (2004), for other nearby dark clouds. Table 1 summarizes our results for the mass of the outflowing gas in the various regions previously defined, tabulated .…”
Section: Outflow Mass and Energysupporting
confidence: 90%
“…We assume a maximum fractional abundance of 1.5 × 10 −6 for 13 CO (Frerking et al 1982;Harjunpää et al 2004 are further scaled by a factor k = 16n 2 5 × 10 5 + 16n 2 , (A.2) which depends on the local H 2 density, n (in units cm −3 ). With this scaling, the maximum abundance is reached only at densities above n = 10 3 cm −3 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies find values close to 2 × 10 −6 , like 1.5 × 10 −6 in Taurus and 2.9 × 10 −6 in Ophiuchus (Frerking et al 1982), 2.3 × 10 −6 in IC5146 (Lada et al 1994) or 2.5 × 10 −6 in Perseus (Pineda et al 2008). Harjunpää et al (2004) found values between 0.9−3.5 × 10 −6 in their survey of the three globules B 133, B 335 and L 466. We use an abundance of 10 −6 in our calculations of N(H 2 ) gas that results in a good agreement seen on Fig.…”
Section: The Temperatures and Column Densities Of The Clumpsmentioning
confidence: 96%
“…Since then, the ratio has been examined by Frerking et al (1982) in Taurus and ρ Ophiuchi, Harjunpää et al (1996) in Chamaeleon I, R Corona Australis and Coalsack, Hayakawa et al (1999Hayakawa et al ( , 2001 in the Chamaeleon complex, and by Lada et al (1994), Alves et al (1999), Juvela et al (1997Juvela et al ( , 2002 and Harjunpää et al (2004) in several small globules. These data, reviewed and compared in more detail by Harjunpää et al (2004), show some evidence supporting the correlation of N(C 18 O)/A V with star forming activity. We present the derivation of the N(C 18 O)/A V ratio in Chamaeleon I, and in selected region of Chamaeleon III, with emphasis on the possible difference between star forming and non-star forming regions.…”
Section: Introductionmentioning
confidence: 99%